A red-shifted two-photon-only caging group for three-dimensional photorelease. Issue 10 (15th February 2018) - Becker, Yvonne; Unger, Erik; Fichte, Manuela A. H.; Gacek, Daniel A.; Dreuw, Andreas; Wachtveitl, Josef; Walla, Peter J.; Heckel, Alexander
Abstract : With a new photolabile protecting group – exclusively cleavable by two-photon-excitation – complex light scenarios for three-dimensional uncaging are possible. Abstract : Based on nitrodibenzofuran (NDBF) a new photocage with higher two-photon action cross section and red-shifted absorption was developed. Due to calculations, a dimethylamino functionality (DMA) was added at ring position 7. The uncaging of nucleobases after two-photon excitation (2PE) could be visualized via double-strand displacement in a hydrogel. With this assay we achieved three-dimensional photorelease of DMA-NDBF-protected DNA orthogonal to NDBF-protected strands. While being an excellent 2P-cage, DMA-NDBF is surprisingly stable under visible-light one-photon excitation (1PE). This case of excitation-specific photochemistry enhances the scope of orthogonal photoregulation.